Profile of cognitive impairment and underlying pathology in multiple system atrophy. Issue 3 (15th November 2016) - Koga, Shunsuke; Parks, Adam; Uitti, Ryan J.; van Gerpen, Jay A.; Cheshire, William P.; Wszolek, Zbigniew K.; Dickson, Dennis W.
ABSTRACT: Background: The objectives of this study were to elucidate any potential association between α‐synuclein pathology and cognitive impairment and to determine the profile of cognitive impairment in multiple system atrophy (MSA) patients. To do this, we analyzed the clinical and pathologic features in autopsy‐confirmed MSA patients. Methods: We retrospectively reviewed medical records, including neuropsychological test data, in 102 patients with autopsy‐confirmed MSA in the Mayo Clinic brain bank. The burden of glial cytoplasmic inclusions and neuronal cytoplasmic inclusions were semiquantitatively scored in the limbic regions and middle frontal gyrus. We also assessed concurrent pathologies potentially causing dementia including Alzheimer's disease, hippocampal sclerosis, and cerebrovascular pathology. Results: Of 102 patients, 33 (32%) were documented to have cognitive impairment. Those that received objective testing, deficits primarily in processing speed and attention/executive functions were identified, which suggests a frontal‐subcortical pattern of dysfunction. Of these 33 patients with cognitive impairment, 8 patients had concurrent pathologies of dementia. MSA patients with cognitive impairment had a greater burden of neuronal cytoplasmic inclusions in the dentate gyrus than patients without cognitive impairment, both including and excluding patients with concurrent pathologies of dementia. Conclusions: The cognitive deficits observed in this study were more evident on neuropsychological assessment than with cognitive screens. Based on these findings, we recommend that clinicians consider more in‐depth neuropsychological assessments if patients with MSA present with cognitive complaints. Although we did not identify the correlation between cognitive deficits and responsible neuroanatomical regions, a greater burden of neuronal cytoplasmic inclusions in the limbic regions was associated with cognitive impairment in MSA. © 2016 International Parkinson and Movement Disorder Society